ANALYSIS ON MOBILE PHONE USAGE IMPACTS IN CLASSROOMS FOR STUDENTS - M.AKHILA DEVI, MVP.RAMESH BABU (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
The findings of the present study show that a substantial percentage of students uses the cell phone for more than 4 hours per day; receive on an average 18 calls per day and make about 8 calls daily. The most popular applications are music and games. They feel that cell phones are status symbols and that most of the world is addicted to cell phones. They admit that cell phones provide security when lost or in new places but state that late night conversations do not disturb concentration in the class. About 40 percent of students admit that they would prefer talking to friends on their cell phones rather than parents when they are at home. However, they do not prefer to engage in cell phone conversations when they are in a low mood. There are, however, a number of problems that have arisen when using mobile learning in a language classroom. The smaller screen, for example, makes it difficult to read content and input text with the online keyboard. Technical problems such as difficulty connecting the Internet, hardware failures and software issues are all common problems. Moreover, distractions from students who do not stay focused on the assigned tasks are becoming a classroom management issue as well. Some of the advantages and disadvantages of using mobile devices in a language classroom at a university setting are discussed in this paper